Quantum Mechanical Investigation of the Electric and Thermal Characteristics of Magnetic Compound Fluid as a Semiconductor on Metal Combined with Rubber. (8th June 2011) - Shimada, Kunio
Abstract : By applying our developed intelligent fluid, magnetic compound fluid (MCF), to silicon oil rubber, we have made the MCF rubber highly sensitive to temperature and electric conduction. MCF is useful as an element material in haptic robot sensors and other related devices. By mixing metal particles in the silicon oil rubber and by applying a strong magnetic field to the rubber, high-density clusters of these particles can be formed. In a previous study, we investigated the electric current resulting from the applied voltage. In the present paper, we discuss the capacitance of the MCF rubber. The capacitance as well as the electric current can be explained by quantum theory and behaves as a semiconductor. Regarding the thermal characteristics, in the present paper, the thermal effect on the electric current and the temporary thermal conductivity differ depending on the applied pressure to the MCF rubber and based on the formation of the magnetic clusters. We also explained the tendency of the electric current and the temporary thermal conductivity during the application of heat under low pressure using quantum mechanics theory and clarified the material behavior as a semiconductor based on the thermal characteristics as well as the electric characteristics.